(untitled) (Medicine Today, 2021)
Introduction: There are many Hypertensive disorders in pregnancy like preeclampsia, eclampsia etc. Pre-eclampsia is the most common medical complication of pregnancy associated with increased maternal and infant mortality and morbidity. Some studies have implicated that low serum calcium levels may have a role in pre-eclampsia but other studies failed to find relation between low levels of these trace elements and pre-eclampsia. Materials and Methods: This cross sectional study was carried out in the Department of Biochemistry, Sylhet MAG Osmani Medical College in collaboration with the Department of Obstetrics and Gynaecology, Sylhet MAG Osmani Medical College Hospital during the period from January 2016 to December 2016. This Study was occured in among 31 pre-eclampsia patients, aged 20 to 40 years, and gestational age ranges from 20 to 40 weeks and 31 age matched normotensive non-pregnant women having no proteinuria. Serum magnesium was measured by Colorimetric method. Results: The mean serum magnesium level was 3.24 (±1.42) mg/dl in pre–eclampsia and was 3.30 (±1.5) mg/dl in normal women. The mean serum magnesium level did not differ significantly between the subjects of pre–eclampsia and normal women (t=0; p<.05). Conclusion: The means of both data sets are equal. So we can conclude that there is no significant difference between them. Medicine Today 2021 Vol.33(1): 58-60